2021
DOI: 10.34172/jrhs.2021.66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light on Attention and Reaction Time: A Systematic Review

Abstract: Background: Accuracy, speed, efficiency, and applicability of activities in the workplace are among the most important effective factors on people's productivity, which is in turn affected by environmental factors, such as light. Therefore, the present research aimed to review the studies performed about the effects of light on attention and reaction time. Sudy Design: A systematic review. Methods: This review study systematically searched articles from 2000-2019 in databases of Google Scholar, ISC, SID, Magir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…The influence of the colour of light on human mood, attention, consciousness, and reaction time has been established 77 and it modulates brain responses during cognitive tasks. 78 Notably, the impact of light of different colour has been extensively utilized in the treatment of certain mood disorders. For studying the colour of light-dependent learning responses of human brain, we performed an experiment to observe the light wavelength-dependent of EPSC in these photo synaptic OFETs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the colour of light on human mood, attention, consciousness, and reaction time has been established 77 and it modulates brain responses during cognitive tasks. 78 Notably, the impact of light of different colour has been extensively utilized in the treatment of certain mood disorders. For studying the colour of light-dependent learning responses of human brain, we performed an experiment to observe the light wavelength-dependent of EPSC in these photo synaptic OFETs.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the colour of light on human mood, attention, consciousness, and reaction time has been established 77 and it modulates brain responses during cognitive tasks. 78 Notably, the impact of light of different colour has been extensively utilized in the treatment of certain mood disorders. For studying the colour…”
Section: Human Mood Influencementioning
confidence: 99%
“…These results suggest that positive alpha and low-gamma waves could be key indicators of attentional errors or deficits. Previous studies have demonstrated the positive effects of blue light on attention and consciousness [13] [14] [15]. For instance, exposure to blue-enriched white light (17,000 K) can reportedly improve working memory and sustained attention [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exposure to high levels of illuminance at the eye level can induce subjective alertness and vitality, increase physiological arousal, and improve performance in a sustained attention task even in the absence of sleep and with light deprivation [21]. Generally, high illuminance levels have been associated with increased alertness and concentration, highlighting their importance in enhancing attention [13].…”
Section: Discussionmentioning
confidence: 99%